Retinal nerve fibre layer thickness in a healthy Nepalese population by spectral domain optical coherence tomography - Thapa, Madhu; Khanal, Safal; Shrestha, Gulsan B; Sharma, Ananda K (Nepalese Journal of Ophthalmology, 2014)
Objective: To determine the normal values for peripapillary retinal nerve fibre layer thickness (RNFL) measured by spectral domain optical coherence tomography (SD- OCT) in a healthy Nepalese population and to compare the RNFL thicknesses between the genders and among the various age groups. Material and methods: One hundred and fifty six eyes of 156 healthy Nepalese subjects (66 males and 88 females) of various age groups were enrolled in this observational, cross-sectional, hospital-based study. The peripapillary RNFL of the randomly chosen eye of each subject was imaged with a high resolution SD-OCT (Spectralis HRA+OCT, Heidelberg Engineering). The RNFL thickness was measured around the optic nerve head using 16 automatically averaged, consecutive, circular B scans with a 3.4 mm diameter and compared between the genders and among the various age groups. Results: The mean age of the subjects was 38.94 ± 17.00 years (range - 14 to 76 years). The average peripapillary RNFL was found to be 102.64 ± 9.56 μm (95 % CI 97.01 - 101.93). The mean ± SD peripapillary RNFL measurements at the superior, nasal, inferior and temporal sectors in the study population were 129.51 ± 15.09 μm, 76.55 ± 12.02 μm, 134.53 ± 17.19 μm and 70.74 ± 15.53 μm respectively. The average RNFL thickness was 99.47 ± 10.18 μm in the male whereas it was 105.09 ± 8.31 μm in the female participants. The RNFL decreased by 2.26 μm per age per decade. Conclusion: The Average RNFL thickness is 102.64 ± 9.56 μm in the Nepalese population. Gender and age related variation in the RNFL could serve as a useful guideline in the diagnosis of glaucoma in our population. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11709 Nepal J Ophthalmol 2014; 6(12): 131-139